Brevity and Wit Jerome Robbins in Australia - Shennan, Jennifer (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Jerome Robbins in Australia. The recent celebration of Jerome Robbin's choreography presented by the australian Ballet stretched across more than four decades.